Introduction: Touching the Wounds - M. Therese Lysaught (Journal of Moral Theology)
The paradigm shift toward the wounds of the world as a privileged _locus theologicus_ reverberates throughout this issue of the _Journal of Moral Theology_. Each essay takes as its starting point for analysis and theological development the particularities of different wounds that are simultaneously social, bodily, and ecclesial. From the wounds of depression, moral injury, and trauma, to populist scapegoating in the Philippines and violence in the Niger Delta region of Nigeria, each essay first touches a place of woundedness, interrogates the church and received theology, and from there points in new directions for both moral theology and ecclesial practice.